PENGARUH PENERAPAN GREEN ACCOUNTING DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN PERTAMBANGAN DI INDONESIA - Ditasari, Rollis Ayu; Setyahety, Ririh Anggraini; Aisah, Siti Nur' (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2024)
The Company's value is to maximize business value and shareholder welfare, increasing the wealth of business owners by obtaining maximum profit or profit. This research aims to examine the influence of green accounting and dividend policy on company value with 50 mining companies listed on the Indonesian Stock Exchange (BEI) during the 2018-2022 period. This test uses 35 company data samples using the purposive sampling method. The data analysis method uses multiple linear regression and hypothesis testing. The results of this research indicate that Green accounting and Dividend Policy have no effect on company value.